2021
DOI: 10.3892/etm.2021.9882
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‑derived stem cell sheets combined with β‑tricalcium phosphate/collagen‑I fiber scaffold improve cell osteogenesis

Abstract: Transplantation of cell-based material is a promising approach for the treatment of critical bone defects. However, it is still limited by the lack of suitable scaffold material or abundant seeding cell sources. The present study aimed to establish a novel composite of an adipose-derived stem cell (ADSC) sheet and a synthetic porous β-tricalcium phosphate/collagen-I fiber (β-TCP/COL-I) scaffold to enhance osteogenic activity. ADSCs were isolated from 3-week-old female Sprague Dawley rats and the ADSC sheets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…For example, decellularized trabecular bone (Shridhar et al, 2019) and decellularized ECM from osteogenic‐induced ADSCs (Blum et al, 2021) have been reported to enhance the osteogenic differentiation of ADSCs. Synthetic materials such as β‐tricalcium phosphate/collagen‐I fibre scaffolds (Wang et al, 2021), hydrogel scaffolds (Kim et al, 2020), and PCL‐based nanofibrous composite scaffolds (Mansour et al, 2022) have also been employed to stimulate osteogenic differentiation of ADSCs. Bioactive factors such as growth factors, miRNAs, and exosomes have been harnessed to enhance the osteogenic differentiation of ADSCs (S. Yang et al, 2020; Tan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, decellularized trabecular bone (Shridhar et al, 2019) and decellularized ECM from osteogenic‐induced ADSCs (Blum et al, 2021) have been reported to enhance the osteogenic differentiation of ADSCs. Synthetic materials such as β‐tricalcium phosphate/collagen‐I fibre scaffolds (Wang et al, 2021), hydrogel scaffolds (Kim et al, 2020), and PCL‐based nanofibrous composite scaffolds (Mansour et al, 2022) have also been employed to stimulate osteogenic differentiation of ADSCs. Bioactive factors such as growth factors, miRNAs, and exosomes have been harnessed to enhance the osteogenic differentiation of ADSCs (S. Yang et al, 2020; Tan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, decellularized trabecular bone (Shridhar et al, 2019) and decellularized ECM from osteogenicinduced ADSCs (Blum et al, 2021) have been reported to enhance the osteogenic differentiation of ADSCs. Synthetic materials such as β-tricalcium phosphate/collagen-I fibre scaffolds (Wang et al, 2021), hydrogel scaffolds (Kim et al, 2020), and PCL-based nanofibrous composite scaffolds (Mansour et al, 2022) have also been employed…”
Section: Histological Analysis Of Dfat Cell and Adsc Sheets For Repai...mentioning
confidence: 99%
“…Research finds that ASCs can adhere closely to the scaffold, proliferate, and form high-density bone tissue ( Wang et al, 2021a ). Compared with ASC sheets alone, the expression levels of osteogenic markers ALP, osteocalcin, and osteopontin (OPN) increased significantly ( Wang et al, 2021b ). Another animal experiment showed that the combination of ASCs improved the gap and surrounding ossification of the scaffold compared with the scaffold alone ( Lee et al, 2021 ).…”
Section: Various Ways To Promote Asc Osteogenesis At the Cellular Levelmentioning
confidence: 99%